Association of Bacterial Vaginosis with Vitamin D in Pregnancy: Secondary Analysis from the Kellogg Pregnancy Study - Anna Maya Powell; Judy R. Shary; Christopher Louden; Vishwanathan Ramakrishnan; Allison Ross Eckard; Carol L. Wagner (American Journal of Perinatology Reports, 2019)
Abstract